2011
DOI: 10.3749/canmin.49.6.1505
|View full text |Cite
|
Sign up to set email alerts
|

MINERALOGY OF RARE OCCURRENCES OF PRECIOUS-METAL-ENRICHED MASSIVE SULFIDE IN THE VOISEY'S BAY Ni-Cu-Co OVOID DEPOSIT, LABRADOR, CANADA

Abstract: The Voisey's Bay Ovoid Ni-Cu-Co magmatic sulfide deposit, Labrador, is generally poor in precious metals (Pt, Pd, Ag, Au), but unusual occurrences with elevated levels (Pt + Pd > 0.5 ppm) are present. We present a quantitative description of the precious-metal mineralogy of four such occurrences within massive sulfides. The four samples, all from near the center of the Ovoid, were examined by SEM-based Mineral Liberation Analysis for characterization of precious-metal minerals. Distributions of precious metals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…As shown by the BSE images, the coarse reject sulphides contained a variety of precious and base metal sulphide inclusions. Precious metal (PM) concentrations at Voisey's Bay are typically low compared to other orthomagmatic sulphide deposits, but [21] report discrete PM minerals (e.g., sperrylite, michenerite, Au-Ag, acanthite) in pentlandite, chalcopyrite and pyrrhotite from the Ovoid deposits. Huminicki et al [22] found that Pd was a solid solution component of pentlandite.…”
Section: Discussionmentioning
confidence: 99%
“…As shown by the BSE images, the coarse reject sulphides contained a variety of precious and base metal sulphide inclusions. Precious metal (PM) concentrations at Voisey's Bay are typically low compared to other orthomagmatic sulphide deposits, but [21] report discrete PM minerals (e.g., sperrylite, michenerite, Au-Ag, acanthite) in pentlandite, chalcopyrite and pyrrhotite from the Ovoid deposits. Huminicki et al [22] found that Pd was a solid solution component of pentlandite.…”
Section: Discussionmentioning
confidence: 99%
“…Notes: x = texture observed, -= texture not observed presence or underestimating the amount of microscale precious metal grains due to grain size), and at a much higher resolution compared to common petrographic or exploratory SEM methods (Sylvester, 2012). Although, the application of MLA is often focused in applied mineralogy and metallurgical processes (Fandrich et al, 2007;Ford et al, 2011;Kelvin et al, 2011), heavy mineral provenance in sediments and sedimentary rocks (Lowe et al, 2011;Tsikouras et al, 2011), and till and stream-sediment prospecting (Wilton and Winter, 2012), it can be a strategic tool when used with basic geologic, stratigraphic, mineralogical, and alteration observations to solve genetic problems in the study of metallic mineral deposits.…”
Section: The Application Of Mlamentioning
confidence: 99%
“…Complex trace mineralogy is reported, for example, for uranium (U), silver (Ag), rare earth element (REE) and platinum group element (PGE) ores (e.g. Bowell et al, 2011;Chetty et al, 2009;Grammatikopoulos et al, 2013;Kelvin et al, 2011;Rohde et al, 2014). In such cases a large number of mineral grains, and thus a large number of samples, are measured by automated mineralogy tools (Chetty et al, 2009).…”
Section: Introductionmentioning
confidence: 97%